Classification of ability of mathematics education students of FKIP Syiah Kuala University 2019 viewed from affective and cognitive aspect - Khairul Umam (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The purpose of this study was to analyze where the dominant abilities of prospective teacher students in the Teaching and Education Faculty (FKIP) of Mathematics Education Study Program Letting 2019 lie. This research uses a descriptive quantitative approach with the Library Research method and utilizes written information sources that are officially recognized. The subjects of this study were active undergraduate students (S1) in mathematics education letting 2019 who had taken courses in Mathematics Teaching and Learning Strategies, Mathematical Teaching Evaluation, Mathematical Logic, Linear Algebra and Discrete Mathematics with a total of 54 samples. This study uses data collection techniques by using a questionnaire. The data collected in this study were analyzed by Descriminant Fisher's analysis. This study used discriminant analysis for 2 groups, namely the group with the dominant ability on the affective aspect and the group with the dominant ability on the cognitive aspect. The results of this study indicate that students have more abilities from the affective aspect. The Fisher discriminant function that is formed isEffectiveness = 6.349X1 + 13.821X2 + 16.008X3 + 8.651X4 + 34.332X5Cognitive Aspect = -2.212X1 + 4.890X2 + 25.104X3 + 13.182X4 + 44.945X5